Pendidikan Karakter di Era Millenial - Siregar, Mustamar Iqbal (Al-Ikhtibar: Jurnal Ilmu Pendidikan, 2022)
The discourse on character education is never dry, because until now, Indonesia is still orienting its education towards building national character. But this paper is a little different. Here, the character education model is more flexibly formulated to respond to the reality of the millennial era. Because the presence of the millennial era is a consequence of globalization, it is feared that many parties will weaken the nation's morality and personality. So that with a more flexible formula, it is expected that the millennial generation will be more comfortable following the learning process, without having to lose their ideal character as a generation that is critical, creative, and cultured. With methodological creations this paper tries to offer a model of character education that further suppresses the media-based learning process on four things: scientific honesty, tabayyun method (cross check), encouraging creativity, and building humanist interactions. An educational idea for the millennial generation, which requires the running of an information technology-based education process while being oriented towards character building